Society must be defended : lectures at the Collège de France, 1975-76 - Foucault, Michel (Picador, 2003)
"From 1971 until his death in 1984, Foucault taught at the College de France, one of the most unique and renowned institutions of higher learning in the world. The College enrolls no students and confers no degrees. Professors are required to deliver lectures to the general public on topics from their ongoing original research. During his tenure at the College, Foucault's teaching, which reached audiences that frequently numbered in the thousands, profoundly influenced a generation of scholars." "These lectures, reconstructed from tape recordings and Foucault's own notes, are now being made available in English for the first time. Under the guidance of series editor Arnold I. Davidson, Picador will publish all thirteen volumes of the lectures in North America." "In "Society Must Be Defended," the inaugural volume in the series, translated by David Macey, Foucault traces the genealogy of the problem of war in society from the seventeenth century to the present. Inverting Clausewitz's famous formulation - "War is politics by other means," Foucault explores the notion that "politics is war by other means" in its relation to race, class struggle, and, of course, power. Providing us with a new model of political rationality, he overturns many of our long-held ideas of sovereignty, the law, and even truth itself. The full significance of the dictum "Society must be defended" becomes clear when Foucault's examination culminates in an extraordinary discussion of modern forms of racism."--BOOK JACKET.